Administrative empowerment strategy and its role in crisis management and exceptional circumstances From the point of view of the supervisory leaders of the Coastal Municipalities Water Utility in the Gaza Strip governorates - Abu Mustafa, Muhammad Mustafa; Al-Raqab, Hammad Mahmoud (Journal of Risk and Crisis Management, 2024)
This study aimed to identify the role of the administrative empowerment strategy in crisis management and exceptional circumstances as a survey study on the supervisory leaders of the Coastal Municipalities Water Utility in the governorates of the Gaza Strip. It consists of (30) items, and the study reached a number of results, the most important of which was that there was a great agreement among the study sample about the role of the administrative empowerment strategy in managing crises and exceptional circumstances in the institution, as the general arithmetic mean for all the axes of the questionnaire reached a value of (3.91), The results were in order of priorities that achieved the administrative empowerment strategy as follows: (delegation, participation in decision-making, training, motivating employees, and effective communication). As well as granting sufficient powers to workers to overcome crises and exceptional circumstances.